Demonstration of Secondary Lysosomes in Bovine Megakaryocytes and Platelets Using Acid Phosphatase Cytochemistry with Cerium as a Trapping Agent - Ménard, Michèle; Meyers, Kenneth M; Prieur, David J (Thrombosis and Haemostasis, 1990)
The ultrastructure of lysosomes from bovine megakaryocytes (MK) and platelets was characterized using acid phosphatase cytochemistry with beta-glycerophosphate as substrate and cerium as a trapping agent. The technique was easily reproducible; cerium-phosphate precipitates were uniform, readily visualized, and there was a virtual absence of nonspecific reaction product. Acid phosphatase was localized in the trans aspect of the Golgi complex and/or granules of less than 50 nm to 650 nm diameters in MK at all stages of maturation. Forty percent of the MK lysosomes contained inclusions of variable shapes, sizes and electron-density and were classified as secondary lysosomes. Twenty-four percent of the platelet sections contained acid phosphatase-positive granules. Fifty-four percent of these were secondary lysosomes. This is the initial report demonstrating secondary lysosomes in either resting MK or platelets using acid phosphatase cytochemistry. These findings suggest that MK and platelet lysosomes have an intracellular function in resting MK and platelets.
Keywords: Secondary lysosomes; Bovine Mk and platelets; Acid phosphatase cytochemistry wit cerium